Investigation on Coaxial Multiwavelength Generation in a CVD Diamond Crystal in the Near-IR Regime. (22nd October 2021) - Hao, Jingjie; Lv, Ze; Shen, Yu; Zong, Nan; Tu, Wei; Zhang, Shenjin; Bo, Yong; Peng, Qinjun; Xu, Zuyan
Abstract : Optical properties and high-order stimulated Raman scattering (SRS) generation in a homemade CVD diamond crystal with 3 × 3 mm 2 aperture are investigated in this paper. The high order of the Raman laser has been studied theoretically and demonstrated experimentally. By simulating the Stokes components at different pump intensities and the divergence angles, the pump source was well matched with the size of the crystal. Pumped by using a 1064 nm picosecond laser, five coaxial wavelengths were obtained for the first time based on the CVD diamond at 932 nm, 1064 nm, 1240 nm, 1485 nm, and 1851 nm. This work provides a reference for further development of the optical grade diamond crystal with a large aperture.